1995
DOI: 10.1128/jvi.69.2.1093-1098.1995
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in vivo and in vitro assembly of retroviral capsids from Gag precursor proteins expressed in bacteria

Abstract: The capsid precursor protein (Gag) of Mason-Pfizer monkey virus, the prototype type D retrovirus, has been expressed to high levels in bacteria under the control of the phage T7 promoter. Electron microscopic studies of induced cells revealed the assembly of capsid-like structures within inclusion bodies that formed at the poles of the cells 6 h after induction with isopropyl-␤-D-thiogalactopyranoside (IPTG). The inclusion bodies and enclosed capsid-like structures were solubilized completely in 8 M urea, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 31 publications
7
42
0
Order By: Relevance
“…Previous studies had shown that some Gag‐derived proteins can form particles resembling their respective in vitro assembly products inside bacterial cells (Klikova et al ., 1995; Campbell and Vogt, 1997; Gross et al ., 1998). We therefore analyzed the capacity of ΔMA‐CA‐NC and ΔMA‐CA‐NC(ΔSP1) to form ordered structures in vivo by thin section EM analysis of induced E.coli cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown that some Gag‐derived proteins can form particles resembling their respective in vitro assembly products inside bacterial cells (Klikova et al ., 1995; Campbell and Vogt, 1997; Gross et al ., 1998). We therefore analyzed the capacity of ΔMA‐CA‐NC and ΔMA‐CA‐NC(ΔSP1) to form ordered structures in vivo by thin section EM analysis of induced E.coli cells.…”
Section: Resultsmentioning
confidence: 99%
“…Negative stain and thin section EM confirmed that the particles closely resemble immature and mature HIV‐1 cores, respectively. In vitro assembly of Gag‐derived particles with morphological likeness to immature retroviruses has been described for Rous sarcoma virus (Campbell and Vogt, 1997) and Mason Pfizer monkey virus (Klikova et al ., 1995), but HIV‐1 Gag‐derived proteins yielded only spheres that were significantly smaller than authentic immature cores and often heterogeneous in size (Gross et al ., 1998; von Schwedler et al ., 1998; Campbell and Rein, 1999). As we show here using cryo‐EM analysis, spherical particles generated from ΔMA‐CA‐NC‐SP2 are not only similar to the immature virion in size and shape, but display a virtually identical inner organization.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate assumes a matrix cross‐sectional area similar to that of capsid, and is greater than what would be needed to pack an icosahedron of the same approximate size. While some studies suggest that immature retrovirions display icosahedral symmetry (Nermut et al ., 1994; Klikova et al ., 1995), we have no incontrovertible evidence concerning such an interpretation. Our system may be biased against the formation of an icosohedral‐compatible lattice since MoCA lacks the NC domain, or because we have constrained His‐MoCA protein interactions within a planar monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these approaches have proven difficult, since the virions do not crystallize, preparations do not appear homogeneous, and it is unclear whether mature or immature virus cores have helical or icosohedral symmetry, which would be a great help in image reconstruction (Choi et al ., 1991; Fuller et al ., 1995, 1996). In the absence of homogeneous, in vivo ‐derived virus preparations, several groups have undertaken the analysis of virus‐like particles formed in vitro from Pr gag proteins (Nermut et al ., 1994; Klikova et al ., 1995) or their derivatives (Ehrlich et al ., 1992; Campbell and Vogt, 1995; J.McDermott and E.Barklis, unpublished observations). Such studies have shown that Gag‐derived monomer proteins can assemble to form higher order structures, but, for the most part, resolution has been such that the nature of Gag interprotein contacts remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These systems also became the base for several high throughput assays for screening assembly inhibitors. During the last 20 years, a number of in vitro assembly assays have been established, mainly for HIV-1 (Campbell et al, 2001;Campbell and Rein, 1999;Ehrlich et al, 1992;Gross et al, 2000;Lanman et al, 2002), Mason-Pfizer monkey virus (Bohmova et al, 2010;Klikova et al, 1995;Rumlova-Klikova et al, 2000;Rumlova-Klikova et al, 1999;Ulbrich et al, 2006), Rous sarcoma virus Vogt, 1995, 1997;Purdy et al, 2008Purdy et al, , 2009, and murine leukemia virus (Dolezal et al, 2016;Hadravova et al, 2012;Cheslock et al, 2003). HTS assays for inhibitors of HIV-1 assembly include several methods using purified HIV-1 CA or CA-NC proteins.…”
Section: Assay and Methods For Screening And Evaluating Viral Assemblmentioning
confidence: 99%